Ligninolitic Enzyme Immobilization from Pleurotus ostreatus for Dye and Batik Wastewater Decolorization - Dewi, R. S.; Ilyas, M.; Sari, A. A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Batik wastewater is one of the environmental problems which has become a significant water pollution problem recently. It contains a large variety of synthetic dyes, chemicals, and has high chemical oxygen demand (COD). Synthetic dyes are difficult to degrade and have recalcitrant and toxic characteristics. Dyes can be degraded by ligninolytic enzymes, including laccase (Lac), manganese peroxidase (MnP), and lignin peroxidase (LiP). The immobilized ligninolytic enzyme is effectively used to enhance the degradation of dye wastewater. Pleurotus ostreatus, the most abundant ligninolytic enzyme source, is the candidate to regenerate fungal biomass as the bioremediation agent. Immobilization of ligninolytic enzyme using alginate was observed in this study for its efficiency to decolorize and decrease COD concentration of RBBR dye and Naphtol batik wastewater in different time periods (0, 2, 4, 6, 24, 48, 72 h) and growth conditions (static and agitated). The results show that the Lac, MnP, LnP activities of P. ostreatus are 200.43, 9.714, 12938.60 U/l, respectively. Static conditions within 48 hours exhibit the highest percentage of decolorization of dye. Ligninolytic immobilized from its condition has decolorized RBBR dye up to 75.88%, while the percentage of decolorization of agitated culture is 68.09%. This ligninolytic immobilized has decolorized about 94.867% of batik wastewater within 24 hours under a static condition. It is also able to decrease the COD level of the batik wastewater containing Naphtol dye (504 to 233 mg/l) within 24 hours under a shaking condition. Immobilization of enzyme has been a promising alternative for decolorization of dye and batik wastewater.